Theoretical Study of Reaction Mechanism between N,N-Dimethyl acrylamide and Carbazole Derivatives Catalyzed by Palladium(II) - Jing, Y.; Zhu, Y.Q.; Su, H.; Guo, J.C.; Yang, Y.Q. (Asian Journal of Chemistry, 2017)
The reaction mechanism between N,N-dimethyl acrylamide and carbazole derivatives catalyzed by palladium acetate has been investigated by using density functional theory (DFT) with M06 functional. The computational results indicate that the reaction without catalyst reacts via one pathway with a high energy barrier of 254.57 kJ mol-1. While the reaction can happen through two approaches to generate the same product with the existence of palladium acetate catalysis. Furthermore, the catalyst is better to depart from the product as a whole part. And the determining step of dominant pathway in the Pd-catalyzed reaction is the formation of C-N bond which has an energy barrier of 137.91 kJ mol-1. As a result, palladium catalyst not only changes the reaction mechanism, but also decreases the energy barrier significantly which stimulated the reaction well. This study illustrates the reaction mechanism and has a guiding significance for new catalysts designing.